Ultrastructure and Microanalysis of Root Cementum in Diabetic Patients versus Healthy Patients with Periodontitis - Suliman O. Amro; Hisham I. Othman; Salim M. El-Hamidy (Journal of King Abdulaziz University: Medical Sciences, 2023)
Diabetes itself is not a direct cause of periodontal disease, but rather it facilitates the development of gingivitis and periodontitis through local pathological changes in the oral cavity. The relationship between diabetes and hard dental structure, particularly root surfaces has received far less attention, despite the fact that root surfaces are exposed to multiple pathological factors. The aim of this study is to evaluate the effect of diabetes type 1 and 2 on the mineralization of periodontally diseased root cementum using scanning electron microscope and energy dispersive spectrometry. The sample of this study consisted of 30 periodontally diseased teeth obtained from healthy and diabetic patients’ type 1 & 2, and was classified into three groups. The result of this study showed remarkable root cementum destruction in diabetic group versus control group. In addition to a significant decrease in the mineral contents, especially calcium ions in diseased root cementum of diabetic patients’ type 1, this study concluded that the destruction of root cementum surface and the significant decrease in the calcium contents of the cementum of diabetic patients with periodontitis, may play an essential role of tooth looseness in diabetic patients. Moreover, it will assist to clarify the mechanism of periodontal destruction in diabetic patients.